Correlation of serum neopterin concentrations with disease activity in juvenile dermatomyositis. Issue 2 (August 1993) - De Benedetti, F; De Amici, M; Aramini, L; Ruperto, N; Martini, A
Abstract : Serum neopterin concentrations were measured in 15 patients with juvenile dermatomyositis and their correlation with the severity of muscle impairment was evaluated. Neopterin concentrations were measured by radioimmunoassay. When compared with controls (median 0.75 ng/ml; range 0.33-1.18), serum neopterin concentrations were increased in patients with active juvenile dermatomyositis (median 3.21 ng/ml; range 0.95-13.81), but not in patients during remission (median 0.81 ng/ml; range 0.55-1.34). In horizontal and longitudinal studies, serum neopterin was significantly correlated with the severity of muscle strength impairment, whereas serum muscle enzyme values were not. These data suggest that measurement of serum neopterin may be used, together with clinical examination, to guide the treatment of patients with juvenile dermatomyositis.